Optimalisasi Pengelolaan Informasi di Perpustakaan SMA Negeri 7 Binjai melalui Pemanfaatan Aplikasi Berbasis Website - Ramadhan, Anggia; Nadila Huswatun Hasanah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Libraries are part of the learning resources that every school and college must have. Because students easily search for information or knowledge through the library. This community service aims to socialize Information Management at the SMA Negeri 7 Binjai Library through the Use of Website-Based Applications. This community service method uses a socialization approach to students, female students, and teachers of SMA Negeri 7 Binjai. The results of this study explain that a library is an organization tasked with collecting information, processing, presenting, and serving the information needs of library users. The existence of this web-based library is very helpful for students, students, and teachers in obtaining information more quickly and helping the work of librarians in managing libraries that will be with tens of thousands to hundreds of thousands, even millions of collections, with services covering the school community (students, education staff, and the wider community), so it needs to be supported by an automation system that is futuristic (has a forward reach), so that it can always maintain excellent service.